Contingent Relations: Migrant Wellbeing and Economic Development in Rural Manitoba - Bryan, Catherine (Frontiers in Sociology, 2021)
Drawing on ethnographic fieldwork conducted in rural Manitoba and the Philippines, this paper uses the example of Douglas as a tenuous counter-point to the accounts of exclusion that dominate the scholarship on Temporary Foreign Labour in Canada. This paper draws on multi-sited ethnographic research conducted in Asessippi-Parkland with the region’s newest immigrants—those recruited to ensure the viability of the new, diversified rural regional economy, and more specifically, the tourism and hospitality sector, established (though tenuously) in the 1970s. In 2009, unable to meet its labour needs regionally, a local hotel began recruiting temporary foreign labour. By 2014, the Hotel had recruited 71 workers from the Philippines, most of whom arrived through Canada’s Temporary Foreign Worker Program; others having arrived through the province’s immigration scheme, the Manitoba Provincial Nominee Program (MPNP). A reflection of the ubiquity of globalized Filipino migration, the well-being families of these workers had long been informed by economic development in the Philippines and the centrality of international labour mobility to that state project. What emerges from the data is a simultaneous acceptance and contestation of the conditions of transnational family life, and moreover—reflecting the focus of this special issue—the extent to which migrant well-being shifts in accordance to labour mobility regimes responsive to development. Migrant workers and their families are implicated in these connected, yet differently motivated, state projects. And while particular narratives concerning their contributions come to be valorized and even celebrated, their mental, physical, affective, and relational well-being is often over-looked by those who benefit from their labour and mobility. Of equal importance is the provincial state’s participation in this process through the provision of permanent residency to existing and in-coming migrants. While this benefits individual families, it does not inherently challenge the logics of neoliberalism; rather, drawing on its nuances, it create new possibilities for capital accumulation and exploitation, while offering some protection for select families who are willing and able to abide by the terms established by their employer and the Manitoba state.